Spermatogenic Activity and Sperm Traits in Post-Pubertal and Adult Tomcats (Felis catus): Implication of Intra-Male Variation in Sperm Size - Pintus, Eliana; Kadlec, Martin; Karlasová, Barbora; Popelka, Marek; Ros-Santaella, José Luis (Cells, 2021)
Tomcats are considered to be adults at 1 year of age, although many reach sexual maturity at an earlier age. Nevertheless, we still know little about whether the spermatogenic activity and sperm quality of mature under one-year-old tomcats differ from those of tomcats that are over one-year-old. This study aims to evaluate the spermatogenic activity, sperm traits, and their relationships in mature tomcats at two different ages. Sixteen tomcats showing complete spermatogenesis and spermatozoa in their epididymal caudae were used and classified according to their age as post-pubertal (<1 year old) or adult (˃1 year old). Our results show that adult cats have higher epididymal sperm concentration and lower coefficient of variation in sperm head width and ellipticity than post-pubertal cats. However, they do not differ in their testicular and epididymal mass, spermatogenesis, and sperm traits such as motility, mitochondrial activity, morphology, morphometry, as well as plasma membrane, acrosome, and DNA integrity. Reduced intra-male variation of sperm head ellipticity is associated with higher testis mass, epididymis mass, and sperm concentration. Interestingly, low intra-male variation in sperm head size is associated with increased Sertoli cell function and reduced post-meiotic germ cell loss. These findings increase our knowledge about feline reproductive physiology and provide new insights into the functional significance of low intra-male variation in sperm size and shape in tomcats.
Keywords: kočky; spermatozoa; Spermatogenesis; sperm morphometry; testis; hlavička spermie; spermatogenesis; Sperm Count; Sexual Development; Sperm Motility; sexuální vývoj; Sperm Head; fertilita; věkové faktory; zvířata; Cell Size; Epididymis; motilita spermií; Testis; Male; počet spermií; feline; Fertility; spermatogeneze; epididymis; intra-male variation; biologická variabilita populace; Biological Variation, Population; Cats; Age Factors; Animals; velikost buňky; mužské pohlaví; sexual maturity